Analisis Interaksi Sosial Anak Autis - tya, Sulistya Anugrah; Fitri Siti Sundari; Dendy Saeful Zen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstrack This study uses a Case Study with Qualitative Research. This research was carried out on grade II students of SDN Semeru 6 Bogor City, even semester of May of the 2024/2025 school year. Data collection techniques include observation, interviews, and documentation. The main focus of this study includes the patterns of social interaction of autistic children in the school environment, the factors that influence these interactions, and strategies to overcome barriers to social interaction. The results showed that subjects were often alone, despite showing limited interest in interacting with peers. Subjects are able to respond when their names are called and tend to be sensitive to loud noises. The communication pattern shown is still rigid and formal. Strategies used by teachers to improve children's social interaction skills include habituating verbal communication and a playful approach with peers. This study concludes that support from the surrounding environment, especially teachers, parents and peers, plays an important role in developing the social interaction skills of autistic children. Keywords: Autistic, Social Interaction